The Influence of Digital Leadership, Work-Life Balance, Employee Engagement, and Organizational Learning on Employee Performance with Job Satisfaction as a Moderating Variable - Munir, Munir; Firdaus, Rahmad; Suhardi, Suhardi; Amin, Mat (International Journal of Applied Finance and Business Studies, 2024)
This study examines the influence of digital leadership, work-life balance, employee engagement, and organizational learning on employee performance, with job satisfaction as a moderating variable. Using SEM-PLS analysis on data from 250 employees in Indonesia's technology and service sectors, the findings reveal significant positive effects of digital leadership, employee engagement, organizational learning, work-life balance, and job satisfaction on performance. Job satisfaction positively moderates the relationship between digital leadership, work-life balance, and employee engagement with performance. However, a counterintuitive finding emerges in the interaction between job satisfaction and organizational learning, which weakens performance. This suggests that while job satisfaction amplifies the benefits of adaptive leadership and work-life harmony, it may reduce the efficacy of organizational learning initiatives, potentially due to misalignment with individual needs or contextual factors. The study underscores the necessity for organizations to cultivate technology-adaptive environments, prioritize employee engagement, and design balanced policies that integrate digital leadership with holistic well-being. Policymakers are advised to advocate for labor regulations that strengthen digital leadership capabilities and institutionalize work-life balance frameworks. For future research, longitudinal approaches and contextual variables—such as organizational culture or workload pressures—are recommended to deepen understanding of these dynamics. These insights contribute to human resource management strategies in the digital era, including nuanced approaches to sustaining performance while addressing employee satisfaction